An interaction platform for mechanized tunnelling. Application on the Wehrhahn‐Line in Düsseldorf (Germany) / Eine Interaktionsplattform für maschinelle Tunnelvortriebe. Anwendung am Beispiel der Wehrhahn‐Linie in Düsseldorf. Issue 1 (February 2014) - Schindler, Steffen; Hegemann, Felix; Alsahly, Abdullah; Barciaga, Thomas; Galli, Mario; Lehner, Karlheinz; Koch, Christian
Abstract This paper introduces a holistic product model for the interactive simulation of shield tunnelling machines. The underlying product model is based on the Building Information Modelling methodology and uses the Industry Foundation Classes to classify and structure the captured data. Data from design, measurements and numerical simulation components obtained from four sub‐models (ground, tunnel, tunnel boring machine and building) are stored, classified and organized on commonly available servers. The very heterogeneous data structures found in each individual model are adjusted in advance using georeferencing, transformation or other suitable methods to increase compatibility. In particular, this article describes the methodological design of an interactive product model for mechanized tunnelling in soft soil, including its sub‐models. Performance is demonstrated by a case study using data from the Wehrhahn‐Line subway construction site in Düsseldorf, Germany. Here, the focus is on the verification of the product model and its use in the numerical simulations. The research presented is a central component of the Collaborative Research Center SFB 837 "Interaction Modelling in Mechanized Tunnelling" at the Ruhr University, Bochum. Zur interaktiven Simulation von maschinellen Schildvortrieben wird ein ganzheitliches Produktmodell vorgestellt. Das Produktmodell basiert auf der Methode des Building Information Modelings und nutzt zur Strukturierung der Daten das Datenaustauschformat Industry Foundation Classes (IFC). Zentral gespeicherte Daten aus Planung, Messungen oder numerischen Simulationen von insgesamt vier Untermodellen (Baugrund, Tunnel, Tunnelvortriebsmaschine und Bebauung) werden klassifiziert und wiederum zur weiteren Nutzung organisiert. Die sehr heterogene Datenstruktur der einzelnen Untermodelle wird im Vorfeld durch Georeferenzierung, Transformation und andere geeignete Verfahren angepasst. Der Beitrag beschreibt den methodischen Aufbau des interaktiven Produktmodells für den Tunnelvortrieb im Lockergestein einschließlich seiner Untermodelle. Die Leistungsfähigkeit zeigt ein Fallbeispiel mit Daten der U‐Bahnbaustelle Wehrhahn‐Linie in Düsseldorf. Hierbei liegt der Schwerpunkt auf der Verifizierung des Produktmodells sowie auf verknüpften Simulationen und übergreifenden Analysen. Die Forschungsarbeiten sind zentraler Bestandteil des Sonderforschungsbereichs SFB 837 "Interaktionsmodelle für den maschinellen Tunnelbau" an der Ruhr‐Universität Bochum.